Innovation in China: The rise of Chinese inventors in the production of knowledge - Rachel Griffith; Helen Miller (Institute for Fiscal Studies (IFS), 2011)
In 2010 China was the world's fourth largest filer of patent applications. This followed a decade of unprecedented increases in investment in skills and Research and Development. If current trends continue China could rank first in the very near future. We provide evidence that the growth in Chinese patenting activity has been accompanied by a growth in Chinese inventors creating technologies that are near to the science base. Part of the success of China has been to attract the investment of foreign multinationals. This is also true for a number of other Emerging Economies. Europe's largest multinational firms increasingly file patent applications that are based on inventor activities located in emerging economies, often working alongside inventors from the firm's home country.
Keywords: F21; F23; O3; 330; China; innovation; offshoring; patents; Forschungs- und Technologiepolitik; Industrieforschung; Innovationspolitik; Patent; Multinationales Unternehmen; Wissenstransfer; Wirtschaftswachstum; China